Turystyczne wykorzystanie krajobrazu kulturowego w gminie Koronowo = Tourist use of the cultural landscape in Gmina Koronowo - Ewa Nowicka; Zbigniew Podgórski; Alicja Gonia (Kazimierz Wielki University, 2015)
Nowicka Ewa, Podgórski Zbigniew, Gonia Alicja. Turystyczne wykorzystanie krajobrazu kulturowego w gminie Koronowo = Tourist use of the cultural landscape in Gmina Koronowo. Journal of Education, Health and Sport. 2015;5(5):413-426. ISSN 2391-8306. DOI 10.5281/zenodo.18035 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A413-426 https://pbn.nauka.gov.pl/works/562072 http://dx.doi.org/10.5281/zenodo.18035 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2015. Revised 18.04.2015. Accepted: 24.05.2015.   Turystyczne wykorzystanie krajobrazu kulturowego w gminie Koronowo Tourist use of the cultural landscape in Gmina Koronowo   Ewa Nowicka, Zbigniew Podgórski, Alicja Gonia   Instytut Geografii, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego, 85-428 Bydgoszcz, ul. Mińska 15 zbigniew.podgorski@ukw.edu.pl     Słowa kluczowe: krajobraz kulturowy, turystyka, gmina Koronowo, metoda inwentaryzacji krajoznawczej, szlaki turystyczne.   Key words: cultural landscape, tourism, Gmina Koronowo, sightseeing inventory method, hiking trails.   Zarys treści   Gmina Koronowo jest powszechnie uznawana za teren atrakcyjnego krajobrazu, cenną i interesującą przestrzeń turystyczną. Predyspozycje obszaru do uprawiania różnych form turystyki potwierdza wynik oceny atrakcyjności wizualnej krajobrazu. W artykule scharakteryzowano zasoby krajobrazu kulturowego gminy Koronowo. Uzyskane wyniki wskazują, że niemal każda miejscowość posiada obiekt o dużej wartości historycznej bądź kulturowej oraz walory krajoznawcze. Znaczna ich część znajduje się w Koronowie, z uwagi na wielkość miasta i jego bogatą historię. Powszechna opinia dowodzi, że Zalew Koronowski stanowi największy walor turystyczny gminy Koronowo. Nie ulega wątpliwości, iż jest on najmocniejszym atutem oraz marką turystyczną. Świadczy o tym m.in. wzrost intensywności ruchu turystycznego w sezonie letnim. Na podstawie wyników analizy SWOT stwierdzono, że gmina Koronowo ma nadal nie w pełni wykorzystany potencjał turystyczny. Fakt ten ze względu na przeciętną wielkość presji turystycznej potwierdza potrzebę dalszych działań na rzecz rozwoju turystyki na analizowanym obszarze.   Abstract The gmina (third tier administrative unit) of Koronowo is widely regarded an area of attractive landscape, as well as valuable and interesting tourist space. Its suitability for various forms of tourism is confirmed by the assessment of visual attractiveness of the landscape. The article describes the resources of the cultural landscape of Gmina Koronowo. The results indicate that almost every locality has an object of high cultural or historical value as well as sightseeing potential. Most of those objects, however, are located in Koronowo itself, given the size of the town and its rich history. The common opinion proves that the Koronowo Reservoir is the biggest tourist value of Gmina Koronowo. Undoubtedly, it is the strongest asset and a tourist brand. This is evidenced by e.g. intensification of tourist traffic in the summer. Based on the results of the SWOT analysis it was found out that Gmina Koronowo is not fully exploiting its tourism potential. Due to the average size of the tourist pressure, this confirms the need for further action to develop tourism in the analysed area.   Translated by Aleksandara Zaparucha.